A SURVEY ON INTEREST AND READING OF EFL STUDENTS - Male, Hendrikus (PEOPLE: International Journal of Social Sciences, 2019)
Reading plays important skills in language in developing the students’ success in their learning. This study aims to find out if EFL students preferred reading skill. It also intends to determine their interest in learning English in general. It employed a descriptive statistics technique. Data were collected from questionnaires and observation. The result showed that the interest and reading are somewhat varied. The majority of EFL students have no interest in reading other sources like newspaper and magazines and the rest have little interest in reading other sources in general. It also indicated that it is contrary to their statements stating that reading is important to their future. It is concluded that teachers and parents should encourage the students to like reading as well as providing a wide range of reading books so that they may have various sources to read. It could be interesting to consider the awareness of the students. Teachers are then to build and motivate the students’ interest in reading.